2018
DOI: 10.3389/fpsyt.2017.00297
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Dietary Added Sugar Consumption on Striatal Food-Cue Reactivity and Postprandial GLP-1 Response

Abstract: Sugar consumption in the United States exceeds recommendations from the American Heart Association. Overconsumption of sugar is linked to risk for obesity and metabolic disease. Animal studies suggest that high-sugar diets alter functions in brain regions associated with reward processing, including the dorsal and ventral striatum. Human neuroimaging studies have shown that these regions are responsive to food cues, and that the gut-derived satiety hormones, glucagon-like peptide-1 (GLP-1), and peptide YY (PYY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 70 publications
2
41
0
1
Order By: Relevance
“…In conclusion, the concurrence of the neuro-humoral response rather than the individual reactivity enabled successful body weight control. In line with this interpretation, in recent studies an opposing peripheral and central GLP-1 reactivity has been identified following sugar consumption [35] and in obesity [36]. In a caloric restriction setup similar to the first period of our intervention trial, DLPFC cue reactivity was identified to predict weight loss, while hormonal adaptation of leptin and ghrelin were not predictive.…”
Section: Discussionsupporting
confidence: 83%
“…In conclusion, the concurrence of the neuro-humoral response rather than the individual reactivity enabled successful body weight control. In line with this interpretation, in recent studies an opposing peripheral and central GLP-1 reactivity has been identified following sugar consumption [35] and in obesity [36]. In a caloric restriction setup similar to the first period of our intervention trial, DLPFC cue reactivity was identified to predict weight loss, while hormonal adaptation of leptin and ghrelin were not predictive.…”
Section: Discussionsupporting
confidence: 83%
“…Future studies may wish to expand the methodology to include pre-CP test craving levels to rule out any potential confounds. Additionally, while patients reported, and healthcare provider confirmed, no use of the medications that have been previously identified as altering cold tolerance (30). However, we did not complete urine or blood tests for these medications to confirm that participants were not taking these drugs from non-prescribed sources.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…One of the metabolic disorders, obesity, plays an important role in pathogenesis of chronic diseases and is characterized by low-grade inflammation [ 2 ]. Sugar consumption has dramatically increased in the past few decades [ 3 ] due to the wide availability of convenient, high-sugar foods, as well as an abundance of environmental food cues that prime eating behavior [ 4 ]. Overconsumption of sugar is closely linked to obesity and metabolic disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%